Assessment of Market Performance and Influencing Factors of Indian Initial Public Offerings (IPOs) - Agarwal, Anshika; Arya, Purushottam Kumar; Patil, Harshal; Laheri, Vishal Kumar (Indian Journal of Finance, 2025)
Purpose : This study evaluated the short- and long-term market performance of Indian initial public offerings (IPOs) listed on the National Stock Exchange (NSE) between January 2019 and December 2022. The research aimed to assess sector-specific trends, the impact of institutional participation, and the influence of macroeconomic events, particularly the COVID-19 pandemic, on IPO performance. Methodology : The study analyzed a sample of 138 IPOs using quantitative methods, including regression analysis, to determine key factors influencing subscription trends and post-listing performance. Primary and secondary market returns were examined to assess market resilience, with a sector-specific focus on finance and engineering. Findings : The findings revealed that the financial sector demonstrated resilience, maintaining positive returns despite temporary downturns during the COVID-19 crisis. Post-pandemic, IPOs exhibited sustained positive performance. Institutional engagement was identified as a significant determinant of IPO subscription levels. The sector-wise analysis highlighted varying performances, with finance and engineering showing notable results. Practical Implications : The study underscored the importance of institutional participation in IPO performance and provided valuable insights for investors, analysts, and policymakers. Understanding sector-specific trends and macroeconomic influences can enhance investment strategies and market forecasting. Originality : This research contributed to the existing literature by offering a comprehensive assessment of IPO performance in India, particularly during and after a global crisis. It highlighted the sensitivity of IPO returns to external factors and methodological approaches, offering guidance for future investment decisions and policy frameworks.